Development of “My Eyes” Learning Media to Improve Students’ Understanding of the Eye and Its Functions - Hesti Mustika Ati; Sipatun Zahro; N Ilis; Syahroni Syahroni (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2025)
This study aims to develop a concrete learning medium called “My Eyes” to improve fifth-grade elementary school students’ understanding of the structure and functions of the human eye in the IPAS subject. The research employed a Research and Development (R&D) approach based on the stages proposed by Borg and Gall. The process began with a preliminary study conducted at SDIT Attasyakur, which revealed that the average pretest score was 35.94, with most students scoring below the minimum passing grade (KKM) of 75. The development process then proceeded through planning, initial product development, limited testing, revision, and extensive testing in three development schools. The test instrument was analyzed using a validity test (r-count > r-table 0.329) and the Kuder–Richardson reliability formula, resulting in a reliability coefficient (r11) greater than 0.70, indicating that the instrument was reliable. The feasibility of the media was evaluated through questionnaires administered to media experts (improving from 56% to 88% after revision), subject matter experts (87%), teachers (≥80%), and students (categorized as good to very good). The results of the paired-sample t-test involving 54 students showed that the average pretest score of 10.83 increased to 12.02. The t-count value of 12.399 exceeded the t-table value of 1.674 at α = 0.05, indicating a statistically significant difference between students’ scores before and after using the media. The effectiveness analysis also showed an improvement of 18.28%. Therefore, the “My Eyes” learning media is considered feasible, practical, and effective as an instructional tool to enhance students’ understanding of the structure and functions of the human eye in elementary science learning.